Integration of Shipping Law and Maritime Policies in Indonesian Maritime Vocational Education: A Qualitative Assessment of Professional Competency Development - April Gunawan Malau; Yusrial Yusrial (Meteor STIP Marunda, 2025)
This research examines the integration of shipping law and maritime policies within Indonesian maritime vocational education systems, evaluating their effectiveness in developing professional competencies amongst maritime graduates. Employing a qualitative descriptive approach, the study investigates perspectives from three key stakeholder groups: maritime professionals, vocational lecturers, and maritime graduates. The research addresses critical gaps in legal literacy amongst Indonesian seafarers operating within international jurisdictions. Findings indicate an overall effectiveness score of 9/10 across three key indicators: shipping management, maritime business, and maritime finance with sustainability. However, significant opportunities exist for enhanced case-based learning, practical legal simulations, and contextualised application of international maritime conventions. The study recommends systematic curriculum reforms incorporating experiential learning methodologies, strengthened industry-academia collaboration, and development of competency-based legal literacy frameworks aligned with International Maritime Organisation (IMO) standards.